2017
DOI: 10.3389/fmicb.2017.00516
|View full text |Cite
|
Sign up to set email alerts
|

NapA Mediates a Redox Regulation of the Antioxidant Response, Carbon Utilization and Development in Aspergillus nidulans

Abstract: The redox-regulated transcription factors (TFs) of the bZIP AP1 family, such as yeast Yap1 and fission yeast Pap1, are activated by peroxiredoxin proteins (Prxs) to regulate the antioxidant response. Previously, Aspergillus nidulans mutants lacking the Yap1 ortholog NapA have been characterized as sensitive to H2O2 and menadione. Here we study NapA roles in relation to TFs SrrA and AtfA, also involved in oxidant detoxification, showing that these TFs play different roles in oxidative stress resistance, catalas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 89 publications
3
33
0
2
Order By: Relevance
“…Our previous work demonstrated that enaA expression is independent of CrzA 16 . AtfA of A. nidulans was characterized as a candidate transcription factor acting downstream of HogA/SakA MAPK and playing a role in oxidative and osmotic stress responses 19,38,44 . Expression of enaA has been shown to be independent of AtfA, but enaB and enaC displayed AtfA-dependent expression especially in response to oxidative stress 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work demonstrated that enaA expression is independent of CrzA 16 . AtfA of A. nidulans was characterized as a candidate transcription factor acting downstream of HogA/SakA MAPK and playing a role in oxidative and osmotic stress responses 19,38,44 . Expression of enaA has been shown to be independent of AtfA, but enaB and enaC displayed AtfA-dependent expression especially in response to oxidative stress 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Our work has been oriented to demonstrate that ROS play critical signaling roles in cell differentiation (Hansberg and Aguirre, 1990;Aguirre et al, 2005;Mendoza-Martinez et al, 2017;Mendoza-Martínez et al, 2019). In one approach, we have used the filamentous fungi Aspergillus nidulans to study the mechanisms by which cells perceive and respond to external ROS.…”
Section: Introductionmentioning
confidence: 99%
“…However, an ortholog of Tir1 does not exist in the genome of A. fumigatus . In general, Yap1 seems to act not only as an important regulator of the antioxidative stress response, but also as a regulator of several other pathways including carbon utilization and asexual sporulation as shown in Aspergillus nidulans …”
Section: Resultsmentioning
confidence: 99%